THE PARADIGM OF LAW AS A SOCIAL ENGINEERING IN THE EXISTENCE OF CRYPTO ASSET MONITORING: WHAT AND HOW? - Handityo Basworo (Faculty of Law, Universitas Pekalongan, 2023)
The development of transactions through crypto assets is one of the practices carried out in the digital business world. The existence of transactions through crypto assets makes the state regulate and supervise crypto assets. One of the legal policies carried out by the state is to supervise crypto asset transactions by the OJK institution. This study aims to answer two legal issues, namely the implications of regulating crypto asset supervision after the passing of the Law No. 4 of 2023 on Financial Sector Development and Strengthening (PPSK Law) and the orientation of crypto asset supervision after the passing of the PPSK Law from a law perspective as a tool of social engineering. This research is normative legal research by prioritizing conceptual and statutory approaches. The results of the study confirm that the implications of supervising crypto assets after that is to make the existence and position of CoFTRA as a supervisor of transactions using crypto assets increasingly lead to ambiguity because the authority regarding the supervision of crypto assets becomes the authority of the OJK. The orientation of oversight of crypto assets in the perspective of law as a social engineering can be seen that the substance of oversight of crypto assets by the OJK aims to carry out community engineering, namely in the form of future efforts so that the community can optimize crypto asset transactions to increase the strengthening of national finance and to give the public a sense of security for transactions crypto assets carried out, the state took the initiative to formulate oversight of crypto assets by OJK because OJK is considered the right and appropriate institution in efforts to regulate and supervise crypto asset transactions.